IL-17A contributes to reducing IFN-γ/IL-4 ratio and persistence of Entamoeba histolytica during intestinal amebiasis. Issue 6 (December 2017) - Deloer, Sharmina; Nakamura, Risa; Kikuchi, Mihoko; Moriyasu, Taeko; Kalenda, Yombo Dan Justin; Mohammed, Eman Sayed; Senba, Masachika; Iwakura, Yoichiro; Yoshida, Hiroki; Hamano, Shinjiro
Abstract: Amebiasis is an infectious disease caused by Entamoeba histolytica, an anaerobic protozoan parasite, and is a major public health problem worldwide, particularly in areas with inadequate sanitation and poor hygiene. Th1 responses, represented by interferon gamma (IFN-γ), play a protective role by clearing the amebae from the gut, whereas Th2 responses are responsible for chronic infection. Th17 responses preconditioned by vaccination or by modulating the intestinal microbiome protect mice from the settlement of E. histolytica . However, the role of interleukin-17A (IL-17A), which is upregulated during the natural course of intestinal amebiasis, has not been clarified. The aim of this study was to investigate the role of IL-17A during intestinal amebiasis in a mouse model. IL-17A knockout and wild-type CBA/J mice were challenged intracecally with 2 × 10 6 E. histolytica trophozoites, and their infection, pathology, and immune responses were monitored. Neither the initial settlement of E. histolytica nor the inflammation of the cecum was affected by the absence of IL-17A for week 1, but the infection rate and parasite burden declined in a late stage of infection, accompanied by an increased IFN-γ/IL-4 ratio. Therefore, IL-17A contributes to the persistence of E. histolytica and modulates the immune response, including the IFN-γ/IL-4 ratio, which may be responsible for the reduction of the parasite burden in the IL-17A knockout mice during the chronic phase of intestinal amebiasis. Graphical abstract: